Brain in metabolic syndrome model: The effect of exercises and caloric restriction - AKBAY, TUĞBA; ALTURFAN, EBRU IŞIK; ŞENER, GÖKSEL; YARAT, AYŞEN (My University, 2022)
© 2022 Marmara University Press.Caloric restriction (CR) and exercise (EX) have impacts on improving metabolic risk factors. This study aimed to investigate the changes in the brain after EX and/or CR in metabolic syndrome (MeS) induced by a high fructose diet in rats. Sprague-Dawley male rats were divided into five groups. Drinking water including 10% fructose solution was given to rats for 12 weeks to develop a MeS rat model. Animals with MeS were submitted to EX and/or CR for 6 weeks. Blood glucose, and brain tissue damage and antioxidant parameters were measured. Brain lipid peroxidation, sialic acid, mucin, fucose levels increased in the MeS group compared to the control (C) group. These parameters reduced significantly in the metabolic syndrome with caloric restriction (MeS+CR) group, and more significantly in the metabolic syndrome with exercise and caloric restriction group (MeS+EXCR), compared to the MeS group. Glutathione levels, superoxide dismutase and catalase activities decreased in the MeS group compared to the C group, increased both in the MeS+CR group, and MeS+EXCR group compared to the MeS group. High fructose diet consumption can lead to brain tissue damage and decreased antioxidant levels were found to be improved best in the MeS+EXCR group.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; FARMAKOLOJİ VE ECZACILIK; Life Sciences (LIFE); PHARMACOLOGY & TOXICOLOGY; PHARMACOLOGY & PHARMACY; Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); Antioxidant; Brain; Caloric restriction; Exercise; Metabolic syndrome; Oxidative stress